The Anti-social Brain in Schizophrenia: A Role of CaMKII? - El Rawas, Rana; Amaral, Inês M.; Hofer, Alex (Frontiers in Psychiatry, 2022)
Current pharmacological therapy has limited effects on the cognitive impairments and negative symptoms associated with schizophrenia. Therefore, understanding the molecular underpinnings of this disorder is essential for the development of effective treatments. It appears that a reduction in calcium/calmodulin-dependent protein kinase II (α-CaMKII) activity is a common mechanism underlying the abnormal social behavior and cognitive deficits associated with schizophrenia. In addition, in a previous study social interaction with a partner of the same sex and weight increased the activity of α-CaMKII in rats. Here, we propose that boosting of CaMKII signaling, in a manner that counteracts this neuropsychiatric disease without disrupting the normal brain function, might ameliorate the abnormalities in social cognition and the negative symptoms of schizophrenia.